ANALISIS PEMBERDAYAAN SANTRI DALAM PROGRAM PEMBEKALAN SANTRI MANDIRI DI PESANTREN AL-IHSAN KAUMAN KEMIRI KUTOARJO (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
Al-Ihsan Kauman Kemiri Kutoarjo Islamic Boarding School is a non-formal Islamic educational institution that realizes that apart from being equipped with religious knowledge, students need to be provided with various activities that can equip and make them competitive in the economic field. By looking at the potential of the students and the background of each student, Al-Ihsan Islamic Boarding School Kauman Kemiri Kutoarjo implemented an independent student training program. This research aims to analyze the implementation of the independent student training program at Al-Ihsan Islamic Boarding School Kauman Kemiri Kutoarjo so that it can identify problems that arise. arose in the implementation of the independent student training program at the Al-Ihsan Islamic Boarding School. This research is qualitative research. The data analysis techniques used are data collection, data reduction, data verification and presentation as well as drawing conclusions. The results of this research are that the Al-Ihsan Kauman Kemiri Kutoarjo Islamic Boarding School implements an independent student training program well. The implementation of the independent student provision program at the Al-Ihsan Islamic Boarding School refers to empowering human resources. The benefit of having an independent student training program at the Al-Ihsan Kauman Kemiri Kutoarjo Islamic Boarding School is to train and equip students in the field of economics, but on the other hand there are obstacles to the personal character of each student and time constraints regarding the implementation of this program because they have to adjust to study time. them. In order for the independent student training program to run well, it is hoped that there will be time discipline and consistency from all parties involved. It is hoped that the Islamic boarding school will carry out monitoring and evaluation during the course of this program as well as determining the next process for the independent santri training program at the Al-Ihsan Kauman Kemiri Kutoarjo Islamic Boarding School.